2002
DOI: 10.1007/s00267-002-2685-8
|View full text |Cite
|
Sign up to set email alerts
|

Excreta Disposal in Dar-es-Salaam

Abstract: The sociocultural and socioeconomic situation of sanitation in Dar-es-Salaam (Dsm), Tanzania, was studied with explicit emphasis on pit-latrines. Without considering the sociocultural conditions, the so-called best solution might not be the right one. Therefore, in order to achieve the intended goal, a literature review, a questionnaire survey, and personal visits to the chosen study areas were done. In total, 207 household questionnaires were filled in 16 areas of the city. Interviewers did house-to-house vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…It was also found that 79% of the discharge points along the Ocoa River corresponded to domestic sources that were "common areas of domestic dumping" of numerous effluents. This is a common problem in all developing countries where the main problem of water pollution is due to the lack of basic sanitation, and is related to vulnerable sectors of the population that have no options other than polluted rivers as a source for the water they need to conduct essential life functions such as food preparation, personal hygiene, laundry, recreation and sewage services [7,47]. In the municipality of Villavicencio Colombia, domestic sewage (79% of discharge sites) is concentrated and taken to points of discharge without treatment; however, not all homes are connected to the sewer system, because they have septic systems or simply pour wastes directly into a river.…”
Section: Sources Of Pollutants In the River Watermentioning
confidence: 99%
“…It was also found that 79% of the discharge points along the Ocoa River corresponded to domestic sources that were "common areas of domestic dumping" of numerous effluents. This is a common problem in all developing countries where the main problem of water pollution is due to the lack of basic sanitation, and is related to vulnerable sectors of the population that have no options other than polluted rivers as a source for the water they need to conduct essential life functions such as food preparation, personal hygiene, laundry, recreation and sewage services [7,47]. In the municipality of Villavicencio Colombia, domestic sewage (79% of discharge sites) is concentrated and taken to points of discharge without treatment; however, not all homes are connected to the sewer system, because they have septic systems or simply pour wastes directly into a river.…”
Section: Sources Of Pollutants In the River Watermentioning
confidence: 99%
“…A study conducted in Dar es Salaam the largest city in Tanzania gave similar result. It indicated that over 80% of its population of about 3.8m people use pit latrines with about 6% of the dwellers connected to the sewerage system (Chaggu et al, 2002).…”
Section: Wastewater Collectionmentioning
confidence: 99%
“…Urban and rural areas without sewage coverage rely heavily on on-site sanitation systems such as latrines and septic tanks for temporary treatment and disposal of human excreta (Chaggu et al, 2002). The objective of the septic tank is to provide initial treatment to household wastewater by intercepting and separating solid faecal matter from the liquid part.…”
Section: Introductionmentioning
confidence: 99%